2016
DOI: 10.1002/2016jg003499
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralization and immobilization in sediments of the East China Sea: Spatiotemporal variations and environmental implications

Abstract: Nitrogen (N) mineralization and immobilization are important processes of N biogeochemical cycle in marine sediments. This study investigated gross N mineralization (GNM) and NH4+ immobilization (GAI) in the sediments from the East China Sea (ESC), using 15N stable isotope dilution technique. Results show that measured rates of GNM and GAI ranged from 0.04 to 6.1 µg N g−1 d−1 and from undetectable to 9.82 µg N g−1 d−1, respectively. In general, both GNM and GAI rates were significantly greater in summer as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…The measured rates (0.39 to 7.74 nmol N g −1 dry sediment hr −1 ) of nitrogen fixation in this study are comparable to the values reported from other estuarine and coastal sediments (Table ), and the rates are much lower than the denitrification rates (12.04 to 67.13 nmol N g −1 dry sediment hr −1 ) while approximately equivalent to the anammox rates (0.94 to 6.61 nmol N g −1 dry sediment hr −1 ) in the study area (Hou et al, ). If the annual mean rate (1.65 nmol N g −1 dry sediment hr −1 ) of sediment nitrogen fixation obtained in this study is extrapolated to the entire Yangtze Estuary, it is roughly estimated that approximately 1.02 × 10 5 t of nitrogen was fixed annually into the estuarine and coastal environment, given that the bulk density of dry sediment is about 1.19 g cm −3 (Lin et al, ). This calculated amount accounts for about 9.3% of the terrigenous inorganic nitrogen (1.1 × 10 6 t) transported annually into the Yangtze Estuary (Hou et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…The measured rates (0.39 to 7.74 nmol N g −1 dry sediment hr −1 ) of nitrogen fixation in this study are comparable to the values reported from other estuarine and coastal sediments (Table ), and the rates are much lower than the denitrification rates (12.04 to 67.13 nmol N g −1 dry sediment hr −1 ) while approximately equivalent to the anammox rates (0.94 to 6.61 nmol N g −1 dry sediment hr −1 ) in the study area (Hou et al, ). If the annual mean rate (1.65 nmol N g −1 dry sediment hr −1 ) of sediment nitrogen fixation obtained in this study is extrapolated to the entire Yangtze Estuary, it is roughly estimated that approximately 1.02 × 10 5 t of nitrogen was fixed annually into the estuarine and coastal environment, given that the bulk density of dry sediment is about 1.19 g cm −3 (Lin et al, ). This calculated amount accounts for about 9.3% of the terrigenous inorganic nitrogen (1.1 × 10 6 t) transported annually into the Yangtze Estuary (Hou et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…Temperature is an important factor regulating nitrogen transformations, because it affects microbial metabolism directly (Grenon et al, ). The warm season favors the activities of these nitrogen transforming microbes (Jäntti et al, ; Lan et al, ; Lin, Hou, Liu, Li, Zheng, et al, ; Teal et al, ). Interestingly, previous studies reported that temperature is not an important factor controlling the DNRA activity in marine and estuarine sediments (Deng et al, ; Jäntti et al, ; Lisa et al, ; McTigue et al, ), but other studies suggest that higher temperatures enhance DNRA rates in coastal and lacustrine sediments (Brin et al, ; Gardner et al, ; Giblin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gross nitrogen mineralization and NH 4 + immobilization rates were related positively to Eh of overlying water (Table ), mainly because nitrogen mineralization and NH 4 + immobilization processes often occur under aerobic conditions (Updegraff et al, ; Zhou et al, ). NO 3 − is a significant factor regulating the gross nitrogen mineralization because it is an electron acceptor that can oxidate the organic material in aerobic conditions (Lin, Hou, Liu, Li, Zheng, et al, ; Pena et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations